Chronic intermittent hypoxia‐mediated cognitive dysfunction in ovariectomized rats - Emily C. Cheung; Joan B. Escobar; Bridget R. Alber; Caitlin Ribeiro; Ishan Abdullah; Grant Kowalik; Jeannette Rodriguez; Grey Harral; Makeda Melkie; Aman Gill; John T. Ketzenberger; John Bethea; et al. (Experimental Physiology)
Abstract Obstructive sleep apnoea (OSA) is a prevalent cardiorespiratory disorder associated with significant neurocognitive consequences. Despite the higher prevalence of OSA in men, there is a strong association between OSA and Alzheimer's disease (AD), which disproportionately affects women. This study aimed to investigate the impact of chronic intermittent hypoxia (CIH), a hallmark of OSA, on cognitive function and AD markers in ovariectomized, female rats. At 8 weeks of age, 16 Sprague–Dawley rats underwent ovariectomy and were exposed to CIH for 26 weeks. Cognitive function was assessed using the Morris water maze, revealing significant deficits in spatial learning (P < 0.0001) and memory (P = 0.008) in CIH‐exposed rats, compared to controls. Analysis of hippocampal tissue showed increased total tau protein (P = 0.0078), indicative of AD pathology. Additionally, CIH‐exposed rats exhibited respiratory dysfunction characterized by increased frequency of apnoeas (P = 0.0328). These findings provide preclinical evidence of the association between OSA, cognitive decline and AD pathology in females, emphasizing the importance of sex‐specific research in understanding and addressing these pathophysiological interconnections.